PENINGKATAN KETERAMPILAN MENULIS NARASI DENGAN MEDIA GAMBAR ANIMASI DI KELAS IV SD - Ritawati Mahyuddin; Desyandri Desyandri (Universitas Negeri Padang, 2017)
This research departs from the low writing of the narrative of the fourth grade students of the SD Pembangunan Laboratorium UNP. The low writing result is caused by learning method and instructional media used by the teacher. The purpose of this research is to describe the result of learning to write student narrative by using animated picture media. The research approach used is qualitative and quantitative approach. The type of research used is Classroom Action Research (PTK). The subjects of the study were teachers and fourth grade students of SD Pembangunan Laboratorium UNP. The result of the research shows that there is an increase of students' narrative writing result from cycle I average score 69, 8 with 65% completeness to 75,4 with completeness 85%. This increase occurs because of an animated image that matches the character of fourth grade students of elementary school.Keywords: narrative text, animated picture media, elementary school